Technology Adaptation and Human Resources Capacity Problems in Kampung Adat Segunung - Praja Firdaus Nuryananda; Djenggala Prasandi (Nusantara Science and Technology Proceedings, 2023)
This article is the result of a study conducted by the academicians at the Kampung Adat Segunung tourist destination in Carangwulung village, Jombang Regency. This research involves desk studies and field research. Kampung Adat Segunung has adopted digitalization or advanced technology to improve its tourism industry, such as initiating a website, using Instagram (and all the features), and using the loket.com application as an online ticket sales system for Kampung Adat Segunung. However, it turns out that this adaptation effort does not automatically produce significant progress in the Segunung tourism industry. In contrast, the Kampung Adat Segunung are now facing constraints as they rely heavily on third parties to manage their information and communication technology (ICT). Through a descriptive-qualitative methodology, this empirical analysis found that the concept that digitalization and advanced technology (digital technology) adaptation can automatically increase tourism needs to be improved. Digital technology adaptation must be adapted to the context of tourism locations (localization) to be more effective in driving progress. Unfortunately, Kampung Adat Segunung has difficulty addressing the problem, even though the human resources they have are still incapable of adopting digital technology. Data for this study were collected through desk research or literature study, participatory observation, and in-depth interviews with tourism managers in the Kampung Adat Segunung, Jombang.